Can Ipilimumab restore immune response in advanced NSCLC after progression on anti‐PD‐1/PD‐L1 agents?. Issue 8 (16th June 2020) - Sternschuss, Michal; Peled, Nir; Allen, Aaron M.; Dudnik, Elizabeth; Rotem, Ofer; Kurman, Noga; Gal, Omer; Reches, Hiba; Zer, Alona
Abstract : Anti‐PD‐1/PD‐L1 agents play a crucial part in the treatment of non‐small cell cancer (NSCLC) demonstrating improved overall response rate (ORR) and overall survival (OS). Recent studies evaluating combination treatment with anti‐PD‐1 and anti‐CTLA‐4 suggests improved outcome but also increased toxicity. Evidence is scarce regarding subsequent treatment with immune checkpoint inhibitors (ICPI) after progression on anti‐PD‐1/PD‐L1. A total of 15 patients were treated with a combination of anti‐PD1 agent and ipilimumab after confirmed progression of disease on anti‐PD1/PDL1 alone during 2017. Clinical data were retrieved retrospectively. Disease control rate (DCR) was defined as partial response (PR) or stable disease (SD). The overall DCR was 33.3% ( n = 5); two patients with PR and three patients with SD, three of whom had prior documented disease control on anti‐PD1. The immune‐related adverse event (irAE) rate was 40% ( n = 6); two patients had grade 3 AE and one patient died of pneumonitis. While the median time to progression was two months (range 0.5–16), four of the five patients with PR/SD experienced durable benefit for 8–16 months. This small retrospective cohort of heavily pretreated unselected patients suggests ipilimumab might reboost the immune response in patients with advanced NSCLC following progression of disease on anti‐PD1 therapy, while delaying exposure to the higher toxicity rates associated with upfront combination therapy. This strategy should be explored prospectively.